Factors Influencing E-district Adoption: An Empirical Assessment in Indian Context - Baishya, Kuldeep; Samalia, Harsh Vardhan; Joshi, Rohit (International Review of Management and Marketing, 2017)
The purpose of this confirmatory study is to explore the factors influencing the acceptance of e-District services by the citizens in Assam, a north-east state of India. Taking Unified Theory of Acceptance and Use of Technology (UTAUT), Technology Acceptance Model (TAM) and Technology Acceptance Model 3 (TAM3) as the basis, a conceptual framework is developed. The study uses semi-structured interviews, focus groups, and a questionnaire based survey through 166 valid data points to validate the conceptual framework. Moreover, the internal consistency of the scale items is checked with Cronbach's alpha coefficient while the convergent and discriminant validities are checked with multitrait-multimethod matrix. This study confirms the positive relationship of ‘Perceived Usefulness' and ‘Facilitating Conditions' with ‘Behavioral Intention' while the expected positive relationship of ‘Effort Expectancy' and ‘Social Influence' with ‘Behavioral Intention' are found to be insignificant. Also, the study cannot find a significant negative relationship between ‘Computer Anxiety' and ‘Behavioral Intention'. Keywords: E-governance, Adoption, Technology Acceptance Model, Unified Theory of Acceptance and Use of Technology, E-District. JEL Classifications: M00, M15, M38